5′-Degenerate 3′-Dideoxy-Terminated Competitors of PCR Primers Increase Specificity of Amplification. (March 1998) - Atamas, Sergei P.; Luzina, Irina G.; Handwerger, Barry S.; White, Barbara
Amplification of a product in PCR with specific primers may be viewed as an artificial Darwinian-type "selection of the fittest". In other selective systems, such as general evolution, immune system and probably brain cortex, the stringency of selection is not absolute but rather degenerate, with selection of many highly fit units, not limited, however, to only the fittest. In PCR also, annealing of the primers is not absolutely specific. The subsequent amplification frequently leads to amplification of not only the desired product but also to lessspecific sequences. Using theoretical analysis of the degenerate mode of selection, we predict theoretically and prove experimentally that 5′-degenerate, 3′-dideoxy-terminated competitors of PCR primers can be used to dramatically improve the specificity of PCR amplification without affecting the quantitation of the final specific product.